Lone star or team player? The interrelationship of different identification foci and the role of self‐presentation concerns. Issue 2 (5th December 2017) - Searle, Rosalind; Nienaber, Ann‐Marie; Price, Deborah; Holtgrave, Maximilian
Abstract : Work identity is important in the attraction and retention of staff, yet how the facets of such identity relate remains convoluted and unclear despite this being of interest to both scholars and practitioners. We use structural equation modeling to analyze empirical data from 144 employees in the United Kingdom's oil and gas industry, analyzing the nature and interrelationship of identification as individual‐level (career advancement) and social‐level (work group and organization) foci, as well as considering the two psychological self‐presentation factors (value expression and social adjustment) that direct and drive identification processes. A dichotomy between individual and social components of work identity is found, revealing a strong association between both social‐level foci of identification. Moreover, both components of work identity are found to be premised on different psychological factors, furthering our knowledge of the enmeshed nature of identity at work.